Certain Inequalities Involving the Fractional q-Integral Operators - Dumitru Baleanu; Praveen Agarwal (Abstract and Applied Analysis)
We establish some inequalities involving Saigo fractional q-integral operator in the theory of quantum calculus by using the two parameters of deformation, q1 and q2, whose special cases are shown to yield corresponding inequalities associated with Riemann-Liouville and Kober fractional q-integral operators, respectively. Furthermore, we also consider their relevance with other related known results.